Risk factors for asthma exacerbations - Lauri Nordman, MD; Iida Vähätalo, PhD; Leena E. Tuomisto, MD, PhD; Onni Niemelä, MD, PhD; Minna Tommola, MD, PhD; Lauri Lehtimäki, MD, PhD; Pinja Ilmarinen, PhD; Hannu Kankaanranta, MD, PhD (Journal of Allergy and Clinical Immunology: Global)
Background: The Global Initiative for Asthma (GINA) advises evaluation of risk factors for exacerbations. Patients with adult-onset asthma often have a problematic disease presentation with comorbidities. Not much information exists about the prevalence of exacerbation risk factors in adult-onset asthma patients. Objective: We evaluated the prevalence of exacerbation risk factors listed in the 2023 GINA Report and their association with exacerbations in patients with adult-onset asthma. Methods: In the Seinäjoki Adult Asthma Study, 203 patients with adult-onset asthma were followed for 12 years. Data were available for 17 of the 21 GINA risk factors. Exacerbation was defined as an unplanned health care visit with asthma exacerbation mentioned in the medical health records. ClinicalTrials.gov NCT02733016. Results: On average, patients had 3.8 asthma exacerbation risk factors, with poor adherence (54.7%), chronic rhinosinusitis (54.2%), and smoking (52.7%) being the most common. Four patients (2.0%) had no risk factors. Oral corticosteroid use and the number of exacerbations increased with the number of risk factors. Exacerbations were positively associated with gastroesophageal reflux disease (odds ratio [OR], 5.0; 95% confidence interval [CI], 1.7-15.1; P = .004) and age >50 years (OR, 2.3; 95% CI, 1.1-4.8; P = .021) in univariate analyses. After adjustments by sex, pack years, and body mass index, only gastroesophageal reflux disease remained as a statistically significant risk factor (OR, 4.5; 95% CI, 1.5-14.0; P = .009). Conclusions: Exacerbation risk factors are common in patients with adult-onset asthma, and the value of identifying a single risk factor may be low. Patients with multiple risk factors and/or gastroesophageal reflux disease should be emphasized in clinical practice.